2016
DOI: 10.21010/ajtcam.v14i1.14
|View full text |Cite
|
Sign up to set email alerts
|

GEOGRAPHICAL IMPACT ON ESSENTIAL OIL COMPOSITION OF ENDEMICKundmanniaanatolicaHUB.-MOR.(APIACEAE)

Abstract: Background: Kundmannia anatolica Hub.-Mor. is an endemic specie of Apiaceae diversified in Turkey. Several parts of the plant may contain essential oils in different quantity which can be influenced by environmental factors, mainly altitude. The aim of this study was to test whether there is any altitude effect on volatile chemical constituents of essential oil obtained from the fruits of K. anatolica growing spontaneously in different altitudes of Lakes Region in Turkey. Materials and Methods: K. anatolica wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 6 publications
2
27
0
1
Order By: Relevance
“…This difference could be attributed to the different geographical locations which invariably is influenced by different soil and climatic conditions. Our results are consistent with published literature, in that, the quality and quantity of essential oil obtained from plants depend to a large extent on the geographical location and variety of other factors …”
Section: Resultssupporting
confidence: 93%
“…This difference could be attributed to the different geographical locations which invariably is influenced by different soil and climatic conditions. Our results are consistent with published literature, in that, the quality and quantity of essential oil obtained from plants depend to a large extent on the geographical location and variety of other factors …”
Section: Resultssupporting
confidence: 93%
“…Altitudinal variations can bring about significant changes in these factors, which in turn affect the secondary metabolites production in plants. [38] Different studies have shown that the harvesting time and season can also have an impact on the yield and the quantitative composition of essential oils components in plants. [39][40][41] Since all the samples for this study were collected around same time, the effect of harvesting season and time was not applicable in this study.…”
Section: Essential Oil Compositionmentioning
confidence: 99%
“…According to European Pharmacopeia, the EOs can be obtained by steam distillation or by hydrodistillation [ 10 ] and their yield and composition are influenced by the presence of several factors, such as location, climate, plant species, methodology and experimental procedures [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%